2020
DOI: 10.1002/prp2.558
|View full text |Cite
|
Sign up to set email alerts
|

Sultiame pharmacokinetic profile in plasma and erythrocytes after single oral doses: A pilot study in healthy volunteers

Abstract: A pilot study was conducted aiming at specifying sultiame's pharmacokinetic profile, completed by in vitro assays evaluating the intraerythrocytic transfer of sultiame and by a pharmacokinetic model assessing its distribution. Single oral doses of sultiame (Ospolot® 50, 100, and 200 mg) were administered in open‐label to four healthy volunteers. Serial plasma, whole blood, and urine samples were collected. A spiking experiment was also performed to characterize sultiame's exchanges between plasma and erythrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The mean ratio of 2.15 ± 0.78 for zonisamide concurs with the data by D'Urso et al (2.7 ± 0.8; D'Urso, Rudge, et al, 2019) and is also supported by the b/p ratio. For sultiame, to the best of our knowledge, no comparison data between DBS and serum samples are published so far, but it is described that this compound has a strong affinity for erythrocytes (Dao et al, 2020) so that the higher concentrations in DBS seem entirely plausible. For stiripentol, there is neither any comparison data nor information regarding the b/p ratio available, and also during our study period only two sample pairs were received.…”
Section: Resultsmentioning
confidence: 99%
“…The mean ratio of 2.15 ± 0.78 for zonisamide concurs with the data by D'Urso et al (2.7 ± 0.8; D'Urso, Rudge, et al, 2019) and is also supported by the b/p ratio. For sultiame, to the best of our knowledge, no comparison data between DBS and serum samples are published so far, but it is described that this compound has a strong affinity for erythrocytes (Dao et al, 2020) so that the higher concentrations in DBS seem entirely plausible. For stiripentol, there is neither any comparison data nor information regarding the b/p ratio available, and also during our study period only two sample pairs were received.…”
Section: Resultsmentioning
confidence: 99%
“…Data calculated using non-compartmental pharmacokinetic analysis showed that plasma clearance decreased several folds with increasing dose (after 50, 100 and 200 mg and amounted to 40.4, 11.7 and 8.3 L/h) (Table 1). Bioavailability after oral administration was complete and the protein binding was low [65].…”
Section: Sulthiamementioning
confidence: 98%
“…CBZ, PRM and PHT increase the elimination of STM. Antacids with magnesium oxide or magnesium trisilicate and bismuth oxycarbonate decrease GI absorption of STM and, in consequence, decrease plasma levels of STM [19,65]. Serum PHT levels have been shown to increase when STM is added to PHT therapy.…”
Section: Sulthiamementioning
confidence: 99%
“…Interactions CBZ and PRM, PHT increase the elimination of STM. Antacids with magnesium and bismuth decrease gastrointestinal (GI) absorption [38,42]. Therapeutic reference range 2-10 mg/L (5-35 µmol/L) was established for STM [4].…”
Section: Sulthiamementioning
confidence: 99%